Upregulation of Prostaglandin Receptor EP1 Expression Involves Its Association with Cyclooxygenase-2 - Sood, Rapita; Flint-Ashtamker, Galit; Borenstein, Dafna; Barki-Harrington, Liza (PLOS ONE, 2014)
While many signals cause upregulation of the pro-inflammatory enzyme cyclooxygenase -2 (COX-2), much less is known about mechanisms that actively downregulate its expression. We have recently shown that the prostaglandin EP1 receptor reduces the expression of COX-2 in a pathway that facilitates its ubiquitination and degradation via the 26S proteasome. Here we show that an elevation of COX-2 intracellular levels causes an increase in the endogenous expression of prostaglandin EP1. The increase in EP1 levels does not occur at the transcriptional level, but is rather associated with complex formation between the receptor and COX-2, which occurs both in vitro and in mammalian tissues. The EP1-COX-2 complex is disrupted following binding of arachidonic acid to COX-2 and accompanied by a parallel reduction in EP1 levels. We propose that a transient interaction between COX-2 and EP1 constitutes a feedback loop whereby an increase in COX-2 expression elevates EP1, which ultimately acts to downregulate COX-2 by expediting its proteasomal degradation. Such a post translational mechanism may serve to control both the ligand-generating system of COX-2 and its reception system.